The independent audio describer is dead: Long live audio description! - Fryer, Louise (Journal of Audiovisual Translation, 2018)
Traditional audio description (AD) is giving way to integrated audio description in which media accessibility is no longer an add-on but built in from the start in collaboration with the artistic team. As directors and producers take a greater interest in making their work accessible to audience members with a sensory impairment, how are the power dynamics altered between the stakeholders? The idea of abusive forms of translation advanced by Lewis (1985) and Nornes (1999) is reconsidered, together with the sanctity of the source text (ST). Also assessed is the impact on the role and hence the training needs of the professional audio describer. Using data from research projects developed by Extant, the UK’s leading professional performing arts company of visually impaired people, and from the European research project ADLAB PRO, this paper concludes that a describer’s skills and competences are still required even with the evolution of integrated AD.